The Contribution of Some Soil and Crop Management Practice on Soil Organic Carbon Reserves: Review - Shibabaw, Agegnehu; Alemeyehu, Melkamu (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Soil organic carbon is the most important attribute and chosen as the most important indicator of soil and environment quality and agricultural sustainability. Maintaining of soil carbon stocks and other nutrient proved as the most important challenge of arable lands. It depends on soil type, surrounding climate and long term land use. Studies of various research reports indicates that agricultural management practice; crop rotation, residue management, reduced tillage, green manuring and organic matter amendment has identified for its contribution to the improvement of soil organic matter stocks and some other nutrients.Implementing of reduced or no tillage operation has underlined in increasing organic carbon stock of the soil through delaying of organic matter decomposition and N mineralization.Long term adoption of legume based crop rotation notably increases soil organic carbon and N contents, helped with natural gift of atmospheric nitrogen fixation. Organic sources of fertilizer are reservoirs of plant nutrients and organic carbon, and hence amendment with adequate and quality manure ultimately enhances the soil nutrients and SOC stocks of the soil. In general, soil and crop management practices allow the soil to sequester more atmospheric carbon in to the soil.The circumstances ultimately contribute to agricultural sustainability, environmental and soil quality and mitigation of climate change at large.